2017
DOI: 10.5812/ijp.7649
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Ketoacidosis: Demographic Data, Clinical Profile and Outcome in a Tertiary Care Hospital

Abstract: Background: Diabetic ketoacidosis (DKA) is an acute and life-threatening situation that accounts for the majority of diabetesrelated morbidity and mortality in children and adolescents who suffer from type 1 diabetes mellitus (T1DM). Objectives: To investigate the demographic, clinical characteristics, and outcomes of DKA in young patients with established T1DM and newly diagnosed diabetes in a tertiary referral hospital. Methods: Data from all T1DM patients diagnosed with DKA episodes in the pediatric endocri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 27 publications
5
13
1
Order By: Relevance
“…More than three-quarter of the children with DKA were males; similar to the reports from India [26] and Ethiopia [19]. However, the majority of other studies reported female preponderance [5,14,17,24,27]. The reason for this disparity in gender is not clear but could be because infection was a major triggering factor of DKA in our study, similar to the Indian [26] and Ethiopian study [19]; given the biological and genetic vulnerability of males to infection [28], which also tends to be severe in them, thus resulting in infection-caused inflammation, pro-inflammatory cytokine release, and counter-regulatory hormones that lead to insulin resistance/deficiency and metabolic deterioration to DKA [25].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…More than three-quarter of the children with DKA were males; similar to the reports from India [26] and Ethiopia [19]. However, the majority of other studies reported female preponderance [5,14,17,24,27]. The reason for this disparity in gender is not clear but could be because infection was a major triggering factor of DKA in our study, similar to the Indian [26] and Ethiopian study [19]; given the biological and genetic vulnerability of males to infection [28], which also tends to be severe in them, thus resulting in infection-caused inflammation, pro-inflammatory cytokine release, and counter-regulatory hormones that lead to insulin resistance/deficiency and metabolic deterioration to DKA [25].…”
Section: Discussionsupporting
confidence: 80%
“…Diabetic ketoacidosis can occur at disease onset; before T1D is recognised or diagnosed, it can also occur in known patients with T1D (established diabetes), particularly during intercurrent illnesses, and especially, if selfmonitoring is unavailable, insulin is unaffordable or not being provided correctly [4]. Diabetic ketoacidosis may also occur due to poor metabolic control, inappropriate interruption of insulin pump therapy, psychiatric disorders, difficult family circumstances and lower socioeconomic status [5]. There is wide geographic variation in the frequency of DKA at onset of diabetes and rates inversely correlate with regional incidence of TID [3,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, we included studies which described both children who had known T1D and those with a new diagnosis of T1D. However, these studies only included a small number of children with non-T1D (33) or with established T1D (45). Thirdly, studies used different age categories (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 20 of 25 studies reported that DKA was more common in children younger than 5 to 6 years of age compared with older children. In contrast, 5 of 25 studies did not find such an association, including 2 retrospective studies from Iran (35,45), 1 retrospective nationwide study from Sweden (28), 1 prospective multicentre European study (24) and 1 study from the United Kingdom that found a higher risk for DKA only in a subgroup of younger children of Asian origin (23).…”
Section: Identificationmentioning
confidence: 99%